2018
DOI: 10.4081/mm.2017.6998
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the antibacterial and chemical potential of some Beninese pharmacopoiea traditional plants

Abstract: SummaryObjectives. This study aims to evaluate the antibacterial and chemical properties of some medicinal plants used in the fight against enteropathogens in Benin.Methods. Aqueous and ethanolic extracts of Senna siamea, Uvaria chamae, Lantana camara and Phyllantus amarus were tested on 10 bacterial strains. Well diffusion technique, coupled with the microdilution determination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (CMB) was used for antibacterial testing. The larval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Toxicological, chemical and antibacterial (to ten enteropathogens) characterization have been done. This study showed interesting contents in polyphenols and flavonoids and an effective antibacterial activity at 100 mg/mL with Minimal Inhibitory Concentration (MIC) between 100 and 25 mg/mL and inhibition diameters between 7.5 and 21 mm [16].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Toxicological, chemical and antibacterial (to ten enteropathogens) characterization have been done. This study showed interesting contents in polyphenols and flavonoids and an effective antibacterial activity at 100 mg/mL with Minimal Inhibitory Concentration (MIC) between 100 and 25 mg/mL and inhibition diameters between 7.5 and 21 mm [16].…”
Section: Introductionmentioning
confidence: 80%
“…Method described by Legba et al [16] were used. After their collection, the organs (leaves and root) were dried at a temperature of 16°C in the laboratory.…”
Section: Production Of Aqueous and Ethanolic Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Benin, an ethnopharmacological survey performed in Benin identified 57 medicinal plants used by herbalists in the traditional management of Senna siamea (Lam) was one of the most quoted plants [8]. A study performed by Legba et al [9] provided interesting data on the antibacterial activity of Senna siamea on enteric pathogens, and its chemical and toxicological characteristics. In addition, several authors demonstrated in vitro anti-Salmonella activity of S. siamea.…”
Section: Introductionmentioning
confidence: 99%